Technical Directing in Arts and Media Production: Ensuring Credibility - Kareeem Kolawole Ganiyu; Babatunde Covenant Olugbenga; Emmanuel Godwin Kalu (Britain International for Academic Research (BIAR-Publisher), 2025)
An Arts and Media artist is a professional who applies artistic creativity through the media as a tool to convey sociological messages about art and humanity. They work with more modern media beyond traditional artistic drawing such as film, documentary, animation, and design. While assessing the technical directing in Arts and Media production, attention is given to how well the technical equipments: (sound systems, lights, projectors, sets) is used to achieve a successful production. Using a qualitative participant observation, this study dopts John T. Caldwell's Media Production Theory (2008) as a theoritical framework. The study finds out that the utilization of modern technical equipments has enhanced Arts and Media productions in aesthetic terms. Hence there is a recommendation that high-quality technical equipments be used all the time in Arts and Media production to guarantee maximum aesthetic and audience impact.